Bi-diketopyrrolopyrrole (Bi-DPP) as a novel electron accepting compound in low band gap π-conjugated donor–acceptor copolymers/oligomers. Issue 1 (1st January 2017) - Ahner, Johannes; Nowotny, Jürgen; Schubert, Ulrich S.; Hager, Martin D.
Abstract: The synthesis and characterization of a novel 2, 5-diketopyrrolo[3, 4- c ]pyrrole(DPP)-based accepting building block with the scheme DPP-neutral small linker-DPP (Bi-DPP ) is presented, which was utilized as electron accepting moiety for low band gap π-conjugated donor–acceptor copolymers as well as for a donor–acceptor small molecule. The electron accepting moietyBi-DPP was prepared via a novel synthetic pathway by building up two DPP moieties step by step simultaneously starting from a neutral phenyl core unit. Characterization of the synthesized oligomeric and polymeric materials via cyclic voltammetry afford LUMO energy levels from −3.49 to −3.59 eV as well as HOMO energy levels from −5.07 to −5.34 eV resulting in low energy band gaps from 1.52 to 1.81 eV. Spin coating of the prepared donor–acceptor oligomers/polymers resulted in well-defined films. Moreover, UV–vis measurements of the investigated donor–acceptor systems showed a broad absorption over the whole visible region. It is demonstrated thatBi-DPP as an electron accepting moiety in donor–acceptor systems offer potential properties for organic solar cell devices.